The impact of foreign direct investment on GDP growth: The case of Turkey - Mayis Azizov; Yuriy Bilan; Farid Jabiyev; Elvin Alirzayev; Aybeniz Heyderova (Investment Management & Financial Innovations, 2023)
The development of investment processes is significant for a country’s economy, economic development, and the expansion of market opportunities. The successful functioning of the national economy in the global economic space requires its integration into the international finance system. The impact of foreign direct investment on the economy of host countries remains relevant. The purpose of this study is to investigate the impact of foreign direct investments on the Gross Domestic Product of Turkey for the years 1990–2021. The data set includes foreign direct investments, exchange rate levels, and the Gross Domestic Product of Turkey and was used in logarithmic form in the empirical assessments. The results show a positive and statistically significant relationship between foreign direct investments and Gross Domestic Product. A long-term integrative relationship exists between the independent variables (foreign direct investments and exchange rate) and the dependent variable (Gross Domestic Product). Consequently, this implies that a 1% increase in foreign direct investment results in a 0.35% increase in Gross Domestic Product, holding other factors constant.